Green Chemistry Preparation of Canarium Schweinfurthii Activated Carbon/Silver Nanoparticle Composite as Effective Antibacterial Agent for Bacterial Polluted Water Treatment - Boris, Gadjui Youatou; Odogu, Ankoro Naphtali; Daouda, Kouotou; Keilah, Lunga Paul; Nsami, Ndi Julius; Manga, Ngomo Horace; Mbadcam, Ketcha Joseph (European Journal of Applied Sciences, 2026)
Targeting contaminated water containing dye and bacteria is primordial to humans. The adsorption technique has been efficient, but an added antibacterial proper is prime to modern-day functioning. Silver nanoparticles provide an excellent platform for biological and material applications due to their unique physical and chemical properties. Three potential materials were prepared namely Canarium schweinfurthii activated carbon (CSAC), Silver nanoparticles (AgNP) and Canarium schweinfurthii activated carbon/Silver nanoparticles (CSAC/AgNP). Canarium schweinfurthii (CS) precursors were subjected to thermogravimetric analysis (TGA), CSAC material was characterized by scanning electron microscopy-energy dispersive spectrometry (SEM-EDS), X-ray fluorescence (XRF), Fourier transformed infrared spectroscopy (FT-IR) and nitrogen adsorption/desorption (N2-BET) and the AgNP was investigated using UV-Visible analysis. The UV-visible analysis of the nanoparticle shows a strong surface Plasmon resonance peak at 471 nm; the CSAC sample presented high methyl orange (MO) dye uptake varying from 48.293 to 98.328 mg/g. CSAC sample and the extract gave no antimicrobial properties while AgNP and CSAC/AgNP samples exhibited strong antibacterial activities while AgNP had a bactericidal effect on the six bacteria isolates of EC ATCC25922: Escherichia coli ATCC25922; SA ATCC43300: Staphylococcus aureus ATCC 43300; SANR 46003: Staphylococcus aureus NR 46003; S.cho NR-170: Salmonella choleriesus NR-170; SENR 13555: Salmonella enteritica 13555; SENR 4811: Salmonella enteritica 4811.